An effect of lead ions on the growth and oxidative stress of Funaria hygrometrica Hedw. gametophyte on the different stages of development (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
An effect of lead acetate on growth and development of F. hygrometrica gametophyte and indexes of oxidative stress is studied. The toxic effect of lead ions is revealed on all stages of gametophyte development with most sensitivity during gametophore bud formation. Increasing of malonic dialdehyde and carbonylproteins content depending on the age of the moss gametophyte F. hygrometrica is established.
Keywords: lead, protonema, malonic dialdehyde, carbonylproteins, Funaria hygrometrica.